Claiming Innocence - Garrett, Brandon L. (2008)
The advent of DNA testing technology almost two decades ago transformed how courts review claims of innocence. Our system discarded many of the rules of finality that traditionally barred most postconviction claims of innocence. In recent years almost every state enacted post-conviction DNA statutes, which I survey here. Yet our criminal system still remains at a crossroads and meritorious claims of innocence continue to face great obstacles. State statutes typically exclude entire categories of convicts who might convincingly prove their innocence and state courts often deny access to DNA testing. Meanwhile, the Supreme Court has yet to adopt a constitutional innocence claim, though advances in technology have upended the Court's reasons for failing to do so in Herrera v. Collins. Further, wrongful convictions will continue to place pressure on our criminal justice system. Using longitudinal analysis of post-conviction DNA exonerations over time, I show that more than a quarter occurred in cases in which DNA testing was available at trial, with causes including technological advances and fraud and error relating to the DNA testing itself. Our criminal justice system still lacks sufficient procedures to ensure full access to evidence of innocence at the time of trial, and then fails to properly assess claims of innocence brought during appeals. Absent those front and back end protections, DNA exonerations may persist for decades to come